The Cognition of the World Soul in Plato’s Timaeus (Tim. 37a2-c5) - Jiří Stránský (Profil)
This study focuses on explaining the problem of cognition of the world soul through a detailed analysis of passage 37a2–c5 from Plato’s Timaeus. It is divided into three sections, each dedicated to interpreting a different part of the passage. First, the necessary conditions for the soul to be able to cognize correctly are discussed. Second, it is demonstrated that the world soul’s cognition is essentially discursive. It is further argued that the soul makes two different types of declarations that form a single complex inner speech, allowing the soul to cognize both the corporeal and the intelligible. Finally, it is explained how specific cognitive acts arise from the soul’s inner speech.